Keragaman, Dominasi Tikus Silvatik, Kepadatan Pinjal dan Kewaspadaan Pes di Daerah Fokus Pes di Kecamatan Cepogo Kabupaten Boyolali - Jarohman Raharjo; Tri Wijayanti (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
One of rodent borne diseases that exist in Indonesia is pes with flea as vector and rat as reservoir. The objective of this research were to find out the diversity, dominance of rats, the density of rat and fleas as monitoring efforts for vigilance of plague transmission. The study was conducted in September-October 2016 in Wonodoyo and Kembang Kuning village, Cepogo Sub District of Boyolali District. The research is descriptive with cross sectional approach. Samples collection were conducted by rats survey used single live trap in the silvatic area. The results showed that rats trap success in Wonodoyo village was 3.8% (38 rats) and 1,1% (11 rats) in Kembang Kuning village. Four kind of silvatic rats were Rattus exulans, R. tiomanicus, Niviventer fulvescens and Maxomys surifer. Most of the rats caught (73.68%) in Wonodoyo Village were infested with fleas, while in Kembang Kuning Village it was 27.27%. All of fleas identified as Stivalius cognatus. The specific and general flea index value of S. cognatus in Wonodoyo Village is 2.66; Kembang Kuning Village is 0.45. Early vigilance is very important to do to prevent the transmission of bubonic plague originating from silvatic rats in Cepogo District, particularly in Wonodoyo Village.